King of the wind - Henry, Marguerite (Aladdin Paperbacks, 1948)
Follows the adventures of the Arabian stallion brought to England to become one of the founding sires of the Thoroughbred breed and the mute Arab stable boy who tended him with loyalty and devotion all his life.